Never-frozen liquid plasma transfusion in civilian trauma: a nationwide propensity-matched analysis. Issue 1 (18th July 2021) - Chehab, Mohamad; Ditillo, Michael; Obaid, Omar; Nelson, Adam; Poppe, Brandon; Douglas, Molly; Anand, Tanya; Bible, Letitia; Joseph, Bellal
Abstract : BACKGROUND: Never-frozen liquid plasma (LQP) was found to reduce component waste, decrease health care expenses, and have a superior hemostatic profile compared with fresh frozen plasma (FFP). Although transfusing LQP in hemorrhaging patients has become more common, its clinical effectiveness remains to be explored. This study aims to examine outcomes of trauma patients transfused with LQP compared with thawed FFP. METHODS: Adult (≥18 years) trauma patients receiving early (≤4 hours) plasma transfusions were identified in the Trauma Quality Improvement Program 2017. Patients were stratified into those receiving LQP versus FFP. Propensity-score matching in a 1:2 ratio was performed. Primary outcome measures were mortality and time to first plasma unit transfusion. Secondary outcome measures were major complications and hospital length of stay. RESULTS: A total of 107 adult trauma patients receiving LQP were matched to 214 patients receiving FFP. Mean age was 48 ± 19 years, 73% were male, and median Injury Severity Score was 27 [23–41]. A total of 42% of patients were in shock, 22% had penetrating injuries, and 31% required surgical intervention for hemorrhage control. Patients received a median of 4 [2–6] units of PRBC, 2 [1, 3] units of LQP or FFP, and 1 [0–1] unit of platelets. The median time to the first LQP unit transfused was significantly shorter compared with the first FFP unit transfused (54 [28–79] minutes vs. 98 [59–133] minutes; p < 0.001). Rates of 24-hour mortality (2.8% vs. 3.7%; p = 0.664) and in-hospital mortality (16.8% vs. 20.1%; p = 0.481) were not different between the LQP and FFP groups. Similarly, there was no difference in major complications (15.9% vs. 21.5%; p = 0.233) and hospital length of stay (12 [6–21] vs. 12 [6–23] days; p = 0.826). CONCLUSION: Never-frozen liquid plasma is safe and effective in resuscitating trauma patients. Never-frozen liquid plasma has the potential to expand our transfusion armamentarium given its longer storage time and immediate availability. LEVEL OF EVIDENCE: Therapeutic, Level IV.